2019
DOI: 10.1080/15384047.2019.1598760
|View full text |Cite
|
Sign up to set email alerts
|

Slight advantages of nimotuzumab versus cetuximab plus concurrent chemoradiotherapy in locally advanced esophageal squamous cell carcinoma

Abstract: This study aimed to compare the efficacy of nimotuzumab (Nimo) versus cetuximab (C225) plus concurrent chemoradiotherapy (CCRT) in locally advanced esophageal squamous cell carcinoma (LA-ESCC). A total of 95 patients with LA-ESCC were retrospectively reviewed, including 65 in Nimo and 30 in C225. The results showed that the ORR in Nimo (61.0%; CR 22.0%, 13/59; PR 39.0% 23/59) was slightly higher than that in C225 (43.5%; CR 8.7%, 2/23; PR 34.8%, 8/23) but without significant difference (p = 0.81). The DCR was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Squamous cell carcinomas in the head and neck (HNSC), lung (LUSC), and esophagus (ESCA) have some commonalities: significantly increased EGFR expression, high frequency of EGFR amplification, and low rate of SNV/indel mutations. Targeted therapy with cetuximab or necitumumab (a monoclonal antibody targeting EGFR), along with radiotherapy or chemotherapy, have demonstrated promising efficacy and prolonged OS for locally advanced or recurrent and/or metastatic HNSC [54], ESCA [55‐57], and LUSC [58, 59], which is now a new first‐line treatment option in squamous NSCLC. The clear correlation between EGFR abnormal expression and treatment benefit highlights the importance of molecular profiling and predictive biomarkers for treatment selection.…”
Section: Discussionmentioning
confidence: 99%
“…Squamous cell carcinomas in the head and neck (HNSC), lung (LUSC), and esophagus (ESCA) have some commonalities: significantly increased EGFR expression, high frequency of EGFR amplification, and low rate of SNV/indel mutations. Targeted therapy with cetuximab or necitumumab (a monoclonal antibody targeting EGFR), along with radiotherapy or chemotherapy, have demonstrated promising efficacy and prolonged OS for locally advanced or recurrent and/or metastatic HNSC [54], ESCA [55‐57], and LUSC [58, 59], which is now a new first‐line treatment option in squamous NSCLC. The clear correlation between EGFR abnormal expression and treatment benefit highlights the importance of molecular profiling and predictive biomarkers for treatment selection.…”
Section: Discussionmentioning
confidence: 99%
“…In this meta-analysis, there was no significant improvement in the PFS outcome in the anti-EGFR arm, which was consistent with the results of a previous meta-analysis. 52 A longer PFS was only confirmed for nimotuzumab combination therapy, as also reported by Jing et al 53 The biological characteristics of nimotuzumab differ from those of other anti-EGFR agents, which might explain its different clinical effects.…”
Section: Discussionmentioning
confidence: 54%
“… 52 A longer PFS was only confirmed for nimotuzumab combination therapy, as also reported by Jing et al . 53 The biological characteristics of nimotuzumab differ from those of other anti-EGFR agents, which might explain its different clinical effects.…”
Section: Discussionmentioning
confidence: 99%
“…It inhibits the EGFR-dependent intracellular signaling pathway via binding to the extracellular domain of EGFR ( Hirano and Kato, 2019 ). Many phase 2 clinical trials and retrospective studies had showed that in combination of nimotuzumab to chemotherapy or chemoradiotherapy could achieve effective benefits for advanced and metastatic ESCC ( Saumell et al, 2017 ; Jing et al, 2019 ). Pertuzumab is a humanized monoclonal HER2-targeted antibody which binds to a different epitope on the HER2 receptor protein than trastuzumab ( Shitara et al, 2020 ).…”
Section: Molecular Targeted Therapymentioning
confidence: 99%